2020
DOI: 10.1155/2020/7643737
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Foveal and Parafoveal Microvascular Density and Retinal Vessel Caliber Alteration in Inactive Graves’ Ophthalmopathy

Abstract: Purpose. We aimed to evaluate foveal and parafoveal density using optical coherence tomography angiography and the alteration on the retinal vessel diameter in patients with inactive Graves’ ophthalmopathy compared to age-matched normal population. Materials and Methods. Patients with inactive Graves’ ophthalmopathy (study group) and healthy individuals (control group) were enrolled in the cross sectionally designed study. The optical coherence tomography angiography parameters and retinal vessel diameter meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
(43 reference statements)
2
11
1
Order By: Relevance
“…reported that active TAO patients presented with an increased retinal microvascular density. Akpolat et al [33] demonstrated that the temporal and nasal parafoveal vessel density was significantly higher in inactive TAO group, which was consistent with our results. However, Tehrani et al [34] found active and inactive TAO patients both had significantly lower superficial vessel density in the nasal parafoveal [35] also showed inactive TAO patients had decreased vessel density in the superficial OCT angiogram.…”
Section: Discussionsupporting
confidence: 93%
“…reported that active TAO patients presented with an increased retinal microvascular density. Akpolat et al [33] demonstrated that the temporal and nasal parafoveal vessel density was significantly higher in inactive TAO group, which was consistent with our results. However, Tehrani et al [34] found active and inactive TAO patients both had significantly lower superficial vessel density in the nasal parafoveal [35] also showed inactive TAO patients had decreased vessel density in the superficial OCT angiogram.…”
Section: Discussionsupporting
confidence: 93%
“…[32] reported that active TAO patients presented with an increased retinal microvascular density. Akpolat et al [33] demonstrated that the temporal and nasal parafoveal vessel density was signi cantly higher in inactive TAO group, which was consistent with our results. However, Tehrani et al [34] found active and inactive TAO patients both had signi cantly lower super cial vessel density in the nasal parafoveal sector.…”
Section: Discussionsupporting
confidence: 93%
“…But there was no data about the CAS of the GO patients in Zang et al's study. Akpolat et al reported that only parafoveal macular VD decreased in inactive GO, but they ignored the effects of thyroid hormone, antibody levels and smoking on retinal microvascular measurements in this study [21]. Unfortunately neither of aforementioned studies reported clearly the affects of the smoking on retina and optic disc microvascular perfusion in GO patients.…”
Section: Discussionmentioning
confidence: 67%
“…In these studies, old techniques were used to assess the degree of the disorder and it is impossible to evaluate microvascular structure anyway. Only a few studies can be found in the literature about microvascular structures with OCTA in inactive GO patients [10][11][12]21]. But, these studies did not investigate the effect of smoking as a factor impairing microvascular perfusion in GO.…”
Section: Discussionmentioning
confidence: 99%